Clinical laboratory measurement of direct factor Xa inhibitors: Anti-Xa assay is preferable to prothrombin time assay - Barrett, Yu Chen; Wang, Zhaoqing; Frost, Charles; Shenker, Andrew (Thrombosis and Haemostasis, 2010)
Apixaban and other factor Xa (FXa) inhibitors are in late-stage clinical development for prevention and treatment of thromboembolic diseases. Although routine monitoring will not be required, in certain situations assessment of drug level may be helpful. This study evaluated the suitability of commercially available prothrombin time/international normalised ratio (PT/INR) and anti-FXa activity assays to measure FXa inhibitors in plasma. Twelve PT (ISI 0.89ﺹ1.88) and three anti-Xa assays were evaluated in vitro using human plasma spiked with four FXa inhibitors (0ﺹ2,000 ng/ml). Assay variability and correlation with drug plasma exposure were evaluated in patients with venous thromboembolism (VTE) treated with apixaban. All FXa inhibitors prolonged PT; however, assay sensitivity was dependent on thromboplastin reagents used and FXa inhibitors tested. To achieve a doubling of PT, the concentration of each FXa inhibitor varied 2.6- to 8-fold between thromboplastin reagents. The rank order of a FXa inhibitor’s effect on PT ratio varied across thromboplastin reagents. Conversion to INR increased variability. Different anti-Xa assays showed different dynamic ranges for each FXa inhibitor; however, their rank order was consistent. For apixaban, the dynamic range of <7.8–240 ng/ml, and inter- and intra-assay precision of <6% coefficient of variation by Rotachrom assay appeared suitable for the anticipated apixaban plasma concentrations with 2.5 and 5 mg bid clinical doses. The stronger correlation between apixaban plasma concentration and anti-Xa activity (r2 = 0.88–0.89) compared with PT/INR (r2 = 0.36) in patients undergoing VTE treatment suggested that anti-Xa activity was the better indicator of apixaban plasma concentrations.
Keywords: Apixaban; factor Xa inhibitor; prothrombin time; international normalised ratio; anti-Xa activity